Displacement interference between wild ungulate species: does it occur?. Issue 1 (2nd January 2020) - Ferretti, Francesco; Mori, Emiliano
Abstract : Among mammals, interspecific interference is common in carnivores, primates and rodents, but it seems to be a rare occurrence in ungulate communities. We summarised the knowledge on interspecific displacements through behavioural interactions between ungulate species in temperate areas to evaluate the conditions under which ungulate behavioural competitive interactions may occur. We found 18 studies reporting interspecific behavioural dominance between wild ungulates, for a total of 37 reports of interspecific displacement, involving 15 species. Only eight reports showed over more than 10 displacements. Over 60% reports involved at least one alien species. The larger one displaced the smaller one in 69% reports involving only native species and in 58% reports involving at least one alien species. Among ungulates, resource exploitation rather than behavioural interference seems to be the main mechanism for interspecific competition. Behavioural interference may increase when non-coevolved species come into contact (e.g. alien taxa, or species expanding their distribution range following environmental changes), in turn generating the potential for interspecific competition.